2006
DOI: 10.1159/000094426
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-2 and -9 Expression Correlated with Angiogenesis in Human Adenomyosis

Abstract: Background: Adenomyosis is an important cause of dysmenorrhea and infertility for women all over the world, however, the pathogenesis has not been completely elucidated. The purpose of the study was to investigate the role of matrix metalloproteinases (MMPs) and their relation to angiogenesis in human adenomyosis. Methods: Adenomyotic endometrial specimens were removed by hysterectomy from 68 women with adenomyosis. The control group consisted of 26 normal endometrial specimens. Immunohistochemistry was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 48 publications
2
67
1
5
Order By: Relevance
“…In healthy women, MMP enzyme expression alterations have been identified in the endometrium according to the menstrual cycle phases and have been higher during the secretory cycle phase than during the proliferative phase. In contrast to this finding, MMP enzyme expression in adenomyosis was highest during the proliferative phase and underwent insignificant alterations during the menstrual cycle [12,13] . In this study, a statistically significantly higher blood serum concentration of RCAS1 has been observed in adenomyosis and leiomyoma than in patients with uterine leiomyoma alone in the proliferative cycle phase (p !…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…In healthy women, MMP enzyme expression alterations have been identified in the endometrium according to the menstrual cycle phases and have been higher during the secretory cycle phase than during the proliferative phase. In contrast to this finding, MMP enzyme expression in adenomyosis was highest during the proliferative phase and underwent insignificant alterations during the menstrual cycle [12,13] . In this study, a statistically significantly higher blood serum concentration of RCAS1 has been observed in adenomyosis and leiomyoma than in patients with uterine leiomyoma alone in the proliferative cycle phase (p !…”
Section: Discussioncontrasting
confidence: 80%
“…The invasion of endometrial cells is determined by their capacity to secrete matrix metalloproteinase (MMP) enzymes. It has been shown that the expression of MMP enzymes increases in patients with adenomyosis in comparison with healthy women [12,13] . The maintenance of ectopic endometrial cells within the myometrium can be enabled not only by their invasiveness, but also by their ability to regulate the activity of immune system cells.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have documented that MMP-9 aids angiogenesis through extracellular matrix degradation and release of growth factors (34). Similarly, a positive correlation between the expression of cathepsin B and angiogenesis has been reported (35).…”
Section: Downregulation Of Cathepsin B and Mmp-9 Through Rna Interfermentioning
confidence: 84%
“…-интерлейкина-1, -6, -11 (IL-I, -6, -11) [45,46]; -лейкемияингибирующего фактора (LIF) [47]; -сосудисто-эндотелиального фактора роста (VEGF) [48]; -гепаринсвязывающего эпидермального фак-тора роста (ГС-ЭФР) [49]; -матриксных металлопротеиназ (ММР) и их тканевых ингибиторов (ТIMP) [50]; -интегринов [46,47]; -селектинов [51,52]; -гликоделина A [53]; -кадгеринов [45]; -муцинов [45]; -простагландинов [54]; -белка Ki-67 [55,56]. Перечисленные молекулярные маркеры могут определяться в крови, секрете эндометрия или в са-мой ткани эндометрия, полученной при его биопсии.…”
Section: проблемы репродукции 5 2016unclassified